Distribuição de poros e densidade de latossolos submetidos a diferentes sistemas de uso e manejo - Jorge, Ricardo Falqueto; de Almeida, Cinara Xavier [UNESP]; Borges, Elias Nascentes; Passos, Renato Ribeiro (Universidade Federal de Uberlândia (UFU), 2012)
Man cultivates the soil for centuries, but the intensive business and use of the soils under Cerrado vegetation for agricultural production grew out of the seventies. The objective of this study was to evaluate soil physical characteristics as a function of sampling time and the soil uses in a Cerrado area in Uberlandia City - MG, Brazil. The managements were adopted: degraded pasture (M-1), conventional tillage (M-2), minimum tillage (M-3), tillage absence (M-4), no-tillage (NT) for three years (M-5); NT for nine years (M-6), NT for three years after Pinus (M-7), PD for one year after Pinus (M-8) and Pinus forest (M-9) with 25 years old. The evaluations were conducted in 2002/03 growing season, in two areas. The soils were: area 1, an Oxisol (Red Latosol - LV-1, M-1 through M-5) and area 2, two Oxisols (Red Latosol and Red-Yellow Latosol - LVA and LV-2, M-6 through M-9). The physical attributes studied changed depending of the soil class, sampling time and management systems, with emphasis on the area 2 soils, which, in general, better preserved its main physical attributes. Managements with intense tillage, such as the M-2, are the most soil physically degrade, presenting mostly negative changes to soil bulk density, total porosity, microporosity and macroporosity. Since the systems which promote less tillage, in short term, to preserve desirable physical attributes. The M-9 system had the lowest attributes range, compared to the others.

O homem cultiva a terra há vários séculos, mas o uso intensivo e empresarial dos solos sob vegetação de cerrado para a produção agrícola cresceu a partir da década de setenta. O objetivo desse estudo foi avaliar atributos físicos do solo em função da época de amostragem e dos tipos de usos do solo em área de cerrado no município de Uberlândia- MG, Brasil. Os manejos adotados foram: pastagem degradada (M-1), cultivo convencional (M-2), cultivo mínimo (M-3), ausência de preparo (M-4), plantio direto (PD) 3o ano (M-5); PD 9o ano (M-6), PD de 3o ano pós Pinus (M-7); PD de 1o ano pós Pinus (M-8) e floresta de Pinus (M-9) de 25 anos. As avaliações foram realizadas no ano agrícola de 2002/03, em duas áreas. Sendo a área 1 de solo Latossolo Vermelho (LV-1, M-1 até M-5) e a área 2 de Latossolo Vermelho e Latossolo Vermelho-Amarelo (LVA e LV-2, M-6 até M-9). Os atributos físicos estudados sofreram alterações em função da classe de solo, época de amostragem e dos sistemas de uso, com destaque para os solos da área 2, que, em geral, melhor conservaram os seus principais atributos físicos. Manejos com intensa mobilização do solo, como o sistema M-2, são os que mais degradam fisicamente o solo, tendo apresentado alterações negativas principalmente para a densidade do solo, porosidade total, microporosidade e macroporosidade. Já os sistemas que promovem menor mobilização do solo tendem, em curto prazo, a preservar atributos físicos desejáveis. O sistema de manejo M-9 apresentou a menor variação de atributos, comparado aos demais.
Pore size distribution and soil bulk density in oxisols submitted to different management systems and use
Keywords: Sustainability; No-tillage; Conventional tillage; Cerrado soil; Pinus sp.